Peran Pelayanan Diakonia Terhadap Pertumbuhan Gereja Pada Masa Pandemi Covid-19 - Susila, Tirta; Pradita, Yola (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
One of the three ecclesiastical vocations, namely the ministry of deacons. This service is a concrete mandate from the church and the fulfillment of Christ's mandate in terms of missionary service during the Covid-19 pandemic. The method used is a qualitative method with data sources from field data and literature reviews that discuss the role of deacon services in church growth during the Covid-19 pandemic at the GKE Haleluya Nanga Bulik Congregation. The results showed that the GKE Haleluya Nanga Bulik congregation was involved in deacon services as one of the real and active actions that explained motivation and mutual understanding, both in the form of caricative deacon services, reformative deacon services and transformative deacon services for people in need. Thus, the ministry of deacons has implications for church growth. The positive impact is to strengthen friendship and testimony during the Covid-19 pandemic at the GKE Haleluya Nanga Bulik Congregation. Salah satu dari tiga panggilan gerejawi, yaitu pelayanan diakonia. Pelayanan ini merupakan amanat konkrit dari gereja dan pemenuhan amanat Kristus dalam hal pelayanan misionaris di masa pandemi Covid-19. Metode yang digunakan adalah metode kualitatif dengan sumber data dari data lapangan yang membahas tentang peran pelayanan diakon dalam pertumbuhan jemaat pada masa pandemi Covid-19 di Jemaat GKE Haleluya Nanga Bulik. Hasil penelitian menunjukkan bahwa jemaah GKE Haleluya Nanga Bulik terlibat dalam kebaktian diakon sebagai salah satu tindakan nyata dan aktif yang menjelaskan motivasi dan saling pengertian, baik dalam bentuk pelayanan diakon karikatif, pelayanan diakon reformatif maupun pelayanan diakon transformatif bagi masyarakat yang membutuhkan. Dengan demikian, pelayanan diaken berimplikasi pada pertumbuhan gereja. Dampak positifnya adalah mempererat silaturahmi dan kesaksian di masa pandemi Covid-19 di Jemaat GKE Haleluya Nanga Bulik.